Membumikan Konsep Etika Islam dan Relevansinya dalam Kehidupan Berbangsa dan Bernegara: Telaah Pemikiran Transformatif Abdurrahman Wahid - Wildah Nurul Islami; Moh. Solehuddin (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2020)
Abdurrahman Wahid is one of the pioneers for the realization of Islamic ethical values ??with transformative thinking in interpreting Islamic teachings. Islamic ethics is related to the values ??agreed by the community so that it has relevance in many areas of life, including the fields of religion, politics and leadership, law and human rights, and socio-culture. There are three strategies for developing Islamic ethics in an effort to ground Islamic ethics so that they are expected to be able to overcome social problems in the life of the nation and state in Indonesia. First, the transformation of Islamic ethical values ??into the social realm. Second, the implementation of Islamic ethical values ??in overcoming the problems of minority groups, namely the value of tolerance (respect for differences), the value of love for peace, the value of upholding justice, the value of equality in the eyes of the law and the state, and the value of social care. Third, the orientation of the development of Islamic ethics must be directed at the welfare of the people (al-maslahah al-'ammah).